Cautious Evaluation of Weak SARS-CoV-2 Positive Cases on Xpert Xpress SARS-CoV-2: Formulating a Testing Algorithm in a Hospital Setup - Dama, Tavisha; Shivaprakash, Shashikala; Biyani, Neetu; Chheda, Pratiksha (Archives of Clinical and Medical Case Reports, 2022)
Objectives: Due to the sensitivity of the Xpert Xpress SRAS-CoV-2 kit (LOD-0.0200 PFU/ml) and the presence of residual viral RNA from past infections, reporting of higher Ct values is a challenge. Formulating a testing algorithm became important in order to maintain infection control measures in our facility. Materials and Methods: A retrospective analysis of 747 cases that were tested, between July 2020 to September 2021, by both Xpert Xpress SARS-Cov-2 kit and COVID-19 one-step RT-PCR kit (Meril Diagnostics) (reference method) was carried out. Samples with Ct≥36 on Xpert Xpress SARS-CoV-2 were evaluated further to rule out false positives by correlating with infection history and follow-up data. Data were analysed using Microsoft Excel’s built in Data Analysis Tool Pack capability. Results: When compared with an ICMR approved kit (COVID-19 onestep RT-PCR kit), gold standard, the Xpert Xpress SARS-COV-2 kit was found to have POA of 70.6% (95% CI: 67.2% to 73.8%), PPA of 100% (95% CI: 97.9% to 100%) and NPA of 61.2% (95% CI: 57% to 65.2%). For cases with Ct ranging from 15-35, results were 100% concordant between Xpert Xpress SARS-CoV-2 and rt-PCR (n=388), however, there was a decrease in concordance as the Ct values increased on Xpert Xpress SARS-CoV-2 (288 cases with Ct≥36). Further evaluation of discordant cases (n=212) revealed 21.2% (45/212) had infection history. Of the remaining 167 cases, follow up swabs were obtained for 42.5% (71/167), out of which 8.4% (6/71) were found to have active infections. Conclusions: Xpert Xpress SARS-Cov-2 kit can be used as a point of care device in units where urgent results are important. Using an arbitrary cutoff of Ct-36, a testing algorithm was devised where samples with Ct>36 on Xpert Xpress SARS-CoV-2